2021
DOI: 10.1016/j.jcss.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Computing exact solutions of consensus halving and the Borsuk-Ulam theorem

Abstract: We study the problem of finding an exact solution to the consensus halving problem. While recent work has shown that the approximate version of this problem is PPA-complete [28, 29], we show that the exact version is much harder. Specifically, finding a solution with n agents and n cuts is FIXP-hard, and deciding whether there exists a solution with fewer than n cuts is ETR-complete. We also give a QPTAS for the case where each agent's valuation is a polynomial. Along the way, we define a new complexity class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 35 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…Note that all the steps in the proof can be computed in polynomial time. Thus, as Con-sensusHalving is FIXP-hard [18], we immediately get the following: Corollary 4. PizzaCutting is FIXP-hard.…”
Section: Hardness Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Note that all the steps in the proof can be computed in polynomial time. Thus, as Con-sensusHalving is FIXP-hard [18], we immediately get the following: Corollary 4. PizzaCutting is FIXP-hard.…”
Section: Hardness Resultsmentioning
confidence: 82%
“…Clearly, the construction in the proof above also works for more than n valuation functions. In [18], it was shown that deciding whether n + 1 valuation functions can be bisected with n cuts is ∃R-hard. It thus follows that it is ∃R-hard to decide whether 2n + 2 masses can be bisected by n lines.…”
Section: Hardness Resultsmentioning
confidence: 99%
“…Very recently, Filos-Ratsikas et al [30] strengthened the PPA-hardness result to the case of very simple valuation functions, namely piecewise constant valuations with at most two blocks of value. Deligkas et al [22] studied the computational complexity of the exact version of the problem, and obtained among other results its membership in a newly introduced class BU (for "Borsuk-Ulam" [12]) and its computational hardness for the well-known class FIXP of Etessami and Yannakakis [25]. Very recently, Deligkas et al [21] showed the PPA-completeness of the related Pizza Sharing problem [35], via a reduction from Consensus-Halving.…”
Section: Related Workmentioning
confidence: 99%
“…Besides the applications above, the class FIXP also captures the complexity of other problems, such as branching process and context-free grammars [Etessami and Yannakakis, 2010], equilibrium refinements [Etessami et al, 2014;Etessami, 2021], and more recently the complexity of computing a Bayes-Nash equilibrium in the first-price auction with subjective priors [Filos-Ratsikas et al, 2021]. Besides FIXP, there are some other computational classes that capture the complexity of different fixed point problems, namely the classes BU [Deligkas et al, 2021] and BBU [Batziou et al, 2021] which correspond to the Borsuk-Ulam theorem [Borsuk, 1933], and the class HB [Goldberg and Hollender, 2021], which corresponds to the Hairy Ball theorem [Poincaré, 1882].…”
Section: Related Workmentioning
confidence: 99%